WANPRESTASI, KEGAGALAN TRANSAKSI DAN PERLINDUNGAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Gunawan Widjaja; Viony Kresna Sumantri; Shella Felicia; Raissa Arlyn Manikam (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Default in Electronic Transactions is generally the same as default in general. Forms of Default Through the Internet or Electronic Transactions are: Not doing what is promised to be done; Carry out what was promised, but not in accordance with what was promised; Carry out what was promised but was late and Carry out something that according to the agreement should not be done.